The Correlation Of Fishingtrip Frequencies Of Gillnetter On The Amount Of Logistic Needed In Different Monsoon Seasons - Jonny Zain (Ilmu Perairan (Aquatic Science), 2010)
This study was carried out in March to April 2010 at Dumai fishing base. It aimed to learnthe correlation of fishingtrip frequencies of gillnetter on the amount of logistic needed indifferent monsoon seasons (i.e. north and west monsoon seasons). Field survey methods wereapplied and regression analysis was used for further analysis.The result showed that there were strong correlation between the fishingtrip frequenciesand the logistics needed for both seasons. Moreover, the correlation index of the fishing trips andthe logistics, in term of fuels and ice, was lower in the west monsoon season than the eastmonsoon season. In contrast, the correlation index was bigger in term of the freshwater for thetrips for both monsoon seasons. The linier regression lines for each analysis were Y = 153.34 X –23.044 for Fuels; Y = 255.9 X + 37.785 for Ice; Y = 168.05 X + 6.5913 for freshwater during thewest monsoon, while Y = 159.95 X – 29.826 for fuels; Y = 314.59 X + 61.927 for Ice; and Y=154.47 X – 14381 for freshwater during the east monsoon.Key word: fishing trip frequency, fishing logistic